Epidemiology of invasive pneumococcal disease in Southwest Sweden during the first eleven years after the introduction of general childhood pneumococcal vaccination - Tor Härnqvist; Karin Bergman; Erik Backhaus; Mats Dahl; Helena Kolberg; Caroline Ström Turesson; Malin Olander; Staffan Nilsson; Rune Andersson; Susann Skovbjerg; Johanna Karlsson (PLoS ONE, 2026)
Background Invasive pneumococcal disease (IPD) still causes significant morbidity and mortality. In this study, we describe incidence, risk factors, manifestations, and outcome of IPD in Southwest Sweden during the first eleven years after the introduction of conjugate pneumococcal vaccines in the childhood vaccination program in 2009. Methods Clinical data from 2,288 consecutive episodes of IPD in Region Västra Götaland, Sweden during 2009–2019 were retrospectively collected from medical records. Incidence rates were calculated using population data from the same period. The results were compared to data from three previous studies from the same geographical area with a total follow-up of 56 years. Results The incidence of all IPD episodes in 2009–2019 was 12.8/100,000/year. A very high IPD incidence was seen in patients with multiple myeloma (1,497/100,000) and chronic lymphocytic leukemia (505/100,000). Meningitis occurred in 26% of the IPD episodes in children <2 years compared to 4.3% in the age group ≥65 years (12/46 versus 60/1,403; p < 0.001). The opposite was found for pneumonia, which accounted for 22% of the IPD episodes in children <2 years compared to 77% among the elderly (10/46 vs. 1,085/1,403; p < 0.001). In 604 IPD episodes (26.4%), one or more complications were observed, most commonly parapneumonic effusion and empyema. When data were compared with the previous study period, the IPD incidence in children <2 years declined from 22.5 in 1996–2008 to 10.7 per 100,000 in 2009–2019, while only a modest reduction was observed in adults ≥65 years (from 45.0/100,000 to 41.2/100,000). The overall case fatality rate (CFR) increased from 9.9% in 1996–2008 to 12.9% in 2009–2019, which could be explained by increased patient age and underlying comorbidity. Conclusions A substantial decrease in IPD incidence was seen in infants and young children but not in the elderly during the first eleven years after the introduction of the general childhood pneumococcal vaccination program. Patients with hematological malignancies remain a high-risk group of IPD.